Measurement System of Sugar Content in Liquid Media using Computerized Photodiode Sensor - Misto Misto; Tri Mulyono; Alex Alex (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2016)
It has been made an electronic system for measurement of sugar cane in solution media. This system uses a pin photodiode as a sensor, laser source, optical fiber, an operational amplifier (Op-Amp), analog to digital converter (ADC) of the Arduino, and computers. The main operation of the measurement system is done by the sensor and controlled by computer. The the photodiode sensor sends a signal to a signal processing unit (op-amp) and converted to a digital signal by the ADC. The digital signal is then forwarded for processing and display (computer). We Concluded that the system working well because of the sugar content information can be simultaneously displayed on the monitor .Keywords: sugar content, pin photodiode, computer